Survey of geological and environmental risk areas in the Doutor Laerte Laender, city of Teófilo Otoni-MG (International Journal of Geoscience, Engineering and Technology, 2023)
The city of Teófilo Otoni, including the Doutor Laerte Laender neighborhood (object of this study), located in the northeast region of Minas Gerais, is characterized by socio-spatial inequalities and marked by the history of constant events of landslides and floods. According to the literature, it is possible to know in advance where, under what conditions, and the magnitude of landslides, preventing major accidents and social and economic losses. Given this scenario, the objective of this work is to identify and classify the main areas of geological and environmental risk in the Doutor Laerte Laender neighborhood, located in the municipality. For the assessment of areas and risk determination, the quantitative method proposed by the Ministry of Cities was used, which evaluates the areas of mass movement according to its guidelines. As a result, 03 points of risk areas in the neighborhood were raised. From the proposed analysis, the risk classification R3 (High Risk) was obtained for Points 01 and 02, and the classification R2 (Medium Risk) for Point 03. Therefore, preventive measures in order to minimize the impacts of possible landslides and/or prevent losses are necessary in both points studied. In this way, the present work can contribute to the identification and classification of risk areas in the city of Teófilo Otoni, which has had serious destructive events in its history.